دعاوى الحیازة والملكیة في التشریع الجزائري - هاجر مجامعية; إيمان مرزوقي (My University, 2018)
Summary: Through the foregoing we produce a series of results. * The right of possession entitles the owner to benefit and exploit his possession. * The holder has the right to bring proceedings to protect his possession. * Property rights are collected by all authorities from the use, exploitation and disposition of property. * The owner may exercise his powers over his property in strict accordance with the one for which he was created, extending the scope of the practice to The essential elements of the property are its fruits, products, accessories, height and depth to the extent possible and benefit from them. * Acquisition can be acquired by, inter alia, statutory gains. * Real property is earned through, inter alia, legal conduct such as a contract, including material reality such as testaments and real estate adhesion. * The Algerian legislature regulates tenure in accordance with the following conditions. * Hand position * Ownership intention * The legislator singled out the property for the third proceedings * Claim for entitlement * Non-exposure action * Property suspension action * The third case was allocated for possession * Non-exposure action * Claim for restitution of possession * New Suspension Action ......................... ملخص : من خلال ما تقدم نخرج بجملة من النتائج. * حق الحيازة يخول لصاحبه حق الإنتفاع والإستغلال بحيازته. * يحق للحائز رفع دعاوى لحماية حيازته. *حق الملكية يجمع في يد صاحبه كل السلطات من استعمال واستغلال وتصرف. * للمالك أن يمارس سلطاته على عقاره وفق للغاية التي أنشئ من أجلها فيمتد النطاق الممارسة إلى عناصر العقار الجوهرية ثماره ومنتجاته وملحقاته والعلو والعمق لحد ممكن واالنتفاع بها. * يمكن ان تكتسب الحيازة بعدة طرق منها التقادم المكسب. * تكسب الملكية العقارية بطرق عدة منها ما هو متعلق بالتصرفات القانونية كالعقد الشفعة ومنها ما يكتسب بالواقعة المادية كالوصية وااللتصاق العقاري . * نظم المشرع الجزائري الحيازة وفق الشروط الأتية . * وضع اليد * نية التملك * خص المشرع الملكية بثالث دعاوى * دعوى الإستحقاق * دعوى منع التعرض * دعوى وقف أعمال الملكية * وخصص للحيازة ثالث دعاوى * دعوى منع التعرض * دعوى استرداد الحيازة * دعوى وقف األعمال الجديدة ............................. Résumé : Par ce qui précède, nous produisons une série de résultats. * Le droit de possession permet au propriétaire de bénéficier et d’exploiter sa possession. * Le titulaire a le droit d’intenter des poursuites pour protéger sa possession. * Les droits de propriété sont perçus par toutes les autorités sur l’utilisation, l’exploitation et la disposition des biens. * Le propriétaire peut exercer ses pouvoirs sur ses biens en stricte conformité avec celui pour lequel il a été créé, en étendant le champ d’application de la pratique à Les éléments essentiels de la propriété sont ses fruits, produits, accessoires, hauteur et profondeur dans la mesure du possible et en bénéficient. * L’acquisition peut être réalisée, entre autres, par des gains statutaires. * Les biens immobiliers sont gagnés grâce, entre autres, à une conduite juridique comme un contrat, y compris la réalité matérielle comme les testaments et l’adhésion immobilière. * Le législateur algérien réglemente la tenure selon les conditions suivantes. * Position des mains * Intention de propriété * Le législateur a choisi le bien pour la troisième procédure * Demande d’admissibilité * Mesure non liée au poste * Mesure de suspension de propriété * Le troisième cas a été attribué pour possession * Mesure non liée au poste * Demande de restitution de possession * Nouvelle mesure de suspension